Interventions and expected exchange rates in emerging market economies - Santiago García-Verdú; Manuel Ramos-Francia (Banco de México, 2014)
We study variations in the risk-neutral distributions of the exchange rates in Brazil, Chile, Colombia, Mexico, and Peru due to interventions implemented by these countries. For this purpose, we first estimate the risk-neutral densities of the exchange rates based on derivatives market data, for one-day and one-week horizons. Second, using a linear regression model, we assess possible effects on the distributions of the expected exchange rates due to these interventions. We find little evidence of an effect on the expected exchange rates' means, volatilities, skewness, kurtoses, risk premia, and tails' parameters. In the few cases for which we do find some statistical evidence of an effect, it tends to be short-lived or not economically significant. On the other hand, we find evidence that interventions which objective is to restore and/or assure the proper functioning of exchange rate markets have a higher probability of success. This probability increases as the amount of resources to intervene at the disposal of the central bank increases. Needless to say, there are limits to the methodology we use.
Keywords: E5; F31; G12; C58; 330; Interventions; Exchange Rates; Risk-Neutral Distributions; Generalized Extreme Value Distributions